ENGLISH TEACHERS’ STRATEGIES IN INCREASING STUDENTS’ LEARNING MOTIVATION: A CASE STUDY AT CAKE ENGLISH COURSE KAMPUNG INGGRIS PARE MATARAM - Lalu Sony Jaya; Amrullah; Sahuddin (Program Studi Pendidikan Bahasa Inggris, 2022)
This research was conducted to find out and describe English Teachers’ strategies in increasing the students’ learning motivation. This is a descriptive qualitative study. Data sources were from three English teachers and first level students of Cake English Course Kampung Inggris Pare Mataram. Observation, interview, and questionnaire were used to collect the data from three teachers and students. It also used simple strategies to discuss inquiry strategy, expletory strategy, and instructional strategy applied by teacher in teaching. The results of observation, interview, and questionnaire proved that English teachers’ strategies in teaching have motivated the students to learn English. Based on the findings, it can be concluded that strategies used by the English teachers to increase the students’ learning motivation in teaching English are: speech strategy, discussion strategy, question and answer strategy, punish and reward strategy, homework strategy, group working, approach method, jokes, games, telling story, and using some media. Among those strategies, it is found that inquiry strategy could be used to increase and motivate their students’ learning moderately. The students of Cake English Course Kampung Inggris Pare Mataram have good responses to the English teachers who applied many kinds of strategies in teaching. The responses were shown from the students’ motivation – instrumental or innate - in following the teaching and learning activities.